Supporting WTO and Pathways to the Free Trade Area of the Asia Pacific (FTAAP) - Erlinda M. Medalla; Angelica B. Maddawin (Philippine Institute for Development Studies (PIDS), 2015)
The discussions on the Free Trade Area of the Asia Pacific (FTAAP) have evolved in the Asia-Pacific Economic Cooperation (APEC) meetings since 2004 when the APEC Business Advisory Council (ABAC) presented a study suggesting a possible integration of the Asia-Pacific region. The most recent development in this regard is the support of China during its hosting and the formulation of a roadmap about the APEC's Contribution to the Realization of the FTAAP. The paper revisits the factors that could shape the way forward, and some implications on what position the Philippines should take. In particular, it looks at the emerging mega blocks in the APEC region - the Trans-Pacific Partnership (TPP) and Regional Comprehensive Economic Partnership (RCEP), and possible scenarios. The paper highlights the important role of APEC as venue for discussions to steer the region toward regional integration that is supportive of the WTO and APEC goals, and act as a mechanism for enhancing ECOTECH and capability-building efforts to prepare less developed countries in deeper and wider areas of liberalization.
Keywords: 330; World Trade Organization; Free Trade Area of the Asia Pacific; Asia-Pacific Economic Cooperation (APEC); Trans-Pacific Partnership; Regional Comprehensive Economic Partnership; 2015 APEC hosting